Prospective teacher’s health: reserves of propaedeutic work - Кучерган, Єлизавета Валеріївна (Pedagogy of Higher and Secondary Education, 2017)
The article shows the software problems and skills to release the reserve funds for teacher’s health professional preservation. With their help a teacher, when performing certain software tasks, provides not only diagnostic and medical but health work with teachers and students, and propaedeutical work which has been carried out during mastering the specialty by a future teacher. Hence, every modern teacher should realize the importance of their own health as the most important professional value, the necessary condition for professional activity; clearly understand personal reponsibility and active role in preserving and strengthening their health; have knowledge of the influence of specific educational activities and professional factors on their health. Therefore, it is appropriate and necessary to input to the range of subjects that are part of the cycle of teachers’ professional training, disciplines of health care direction. The main program may be «Pedagogical orthobiosis» as an academic discipline in a teaching education institution; it should be aimed at preserving future teacher’s health by giving modern students necessary knowledge and skills in their health preservation and strengthening, which will help them in the productive professional activity, long, full and harmonious life. The material is aimed at creating such programs and their implementation in the educational process of pedagogical institutions.